How does opportunistic behavior influence firm size? - Christian Cordes; Peter J. Richerson; Richard McElreath; Pontus Strimling (Max Planck Institute of Economics, 2006)
This paper relates firm size and opportunism by showing that, given certain behavioral dispositions of humans, the size of a profit-maximizing firm can be determined by cognitive aspects underlying firm-internal cultural transmission processes. We argue that what firms do better than markets - besides economizing on transaction costs - is to establish a cooperative regime among its employees that keeps in check opportunism. A model depicts the outstanding role of the entrepreneur or business leader in firm-internal socialization processes and the evolution of corporate cultures. We show that high opportunism-related costs are a reason for keeping firms' size small.
Keywords: D21; D23; D01; M14; C61; 330; Theory of the Firm; Transaction Cost Economics; Cultural Evolution; Opportunism; Cooperation